Correlation of Serum LDH Level in Perinatal Ashyxia as a Marker of Hypoxic Ischemic Encephalopathy - Singh, Sandip Kumar; Rijal, Shikha; Giri, Arun (Birat Journal of Health Sciences, 2020)
Introduction: Perinatal Asphyxia is common cause of multiorgan dysfunction in neonates. It leads to significant mortality and morbidity. Serum lactate dehydrogenase (LDH), if measured can differentiate asphyxiated neonates from non-asphyxiated neonates. Objectives: To find whether serum LDH can distinguish an asphyxiated from a non-asphyxiated term neonate. To co-relate serum LDH level in perinatal asphyxia with various stages of HIE and to see whether it can predict mortality. Methodology: This is a prospective study done from June 2018 to May 2019 in NICU of Nobel Medical College, on child with Perinatal Asphyxia. All neonates included in the study underwent thorough clinical and neurological examination. Severity of HIE was done by Sarnat & Sarnat staging criteria. Serum LDH level were measured in all the cases. Statistical analysis was done using SPSS 11. Results: 90 neonates with perinatal asphyxia were enrolled and 30 normal neonates were enrolled as controls. The number of neonates with LDH level > 600U/L was significantly more in cases with perinatal asphyxia group as compared to controls (non-asphyxiated) with ‘p’ < 0.001. Serum LDH level was progressively high in relation to stages of HIE and difference between mean LDH level between neonates expired and survived was statistically significant with ‘p’ <0.001. Conclusion: Serum LDH level is a reliable indicator of perinatal asphyxia and helps to differentiate different stages of HIE.